Dynamics of sea level and land on the Black Sea coast during the twentieth and twenty-first centuries - Andrianova, O.R.; Belevich, R.R.; Skipa, M.I.; Peychev, V. (S. Subbotin Institute of Geophysics of the NAS of Ukraine, 2017)
Trends in the sea level and land on the Black Sea coast were explored by using the average annual sea level data on the set of stations in the period from 1874 to 2015. The common regular feature of temporal variability of interannual fluctuations in the Black Sea was the dominance of wave-like rise with varying intensity stages. The value and intensity of interannual tectonic shifts of coastal land on the Black Sea were estimated during the same period with using the method of water leveling. It is shown that uneven subsidence of coastal land is a mirroring of the sea-level rise. Herein, the processes that are taking place in the coastal land and on the sea bottom are determining the fluctuations in sea level.Long-term variability of the sea level fluctuations on long-term time-series stations (140 years) had the following stages: 1875—1925 — weak lowering with intensity of about – 0,02 to – 0,16 cm/ year; 1926—1965 — intensive sea-level rise + 0,30 cm/year; 1966—1995 — growth with smaller intensity + 0,20 cm/year; 1996—2015 — again lowering with intensity – 0,09 cm/year. The stages of sea level fluctuations on short-term stations are also synchronized in the last decade. The stable lowering of average heights of sea level in the 1996—2015 years was found on 7 of the 10 analyzed stations, and on other 3 stations, the tendency of reducing the intensity of level growth was observed.The short and sharp "discrete peaks" of sea level and similar "fallings" of the sea bottom were found in series of average annual data. These disturbances were observed nearly simultaneously on all the analyzed stations with quasi decade frequency and had cycle time 3—4 years (sometimes up to 5 years) and amplitude up to 10—17 cm (usually 12 cm). Sometimes the discrete peaks of the sea level (as soon as "fallings" of the sea bottom) were observed in pairs